Eleusine indica inhibits early and late phases of herpes simplex virus type 1 replication cycle and reduces progeny infectivity - Rashidah Iberahim,; Norefrina Shafinaz Md. Nor,; Wan Ahmad Yaacob,; Nazlina Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The present study was aimed at determining the compounds available in Eleusine indica methanol extract and the effects on herpes simplex virus type 1 (HHV1) replication cycle and progeny infectivity. Twelve compounds mostly from the flavonoid and phenolic groups were identified by Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) analysis. The effect on replication phases of HHV1 was determined by time-of-addition, time-removal and virus yield reduction assays with expression of selected genes analysed by quantitative Real Time-Polymerase Chain Reaction (qRT-PCR). The extract inhibited plaque formation the most during the first 2 h and at 24 h of infection. Plaque formation inhibition was also noted at all other time points but at lesser percentage. Treatment with E. indica reduced progeny infectivity when treated for 10 h and was dose-dependent. E. indica methanol extract inhibited immediate early, early and late phases of HHV1 replication cycle by modifying the expression of UL54, UL27 and UL30 genes during the infection. Immunostaining of infected cells confirmed that E. indica inhibited mainly Glycoproteins B but not Glycoprotein C and D. Thus, the methanol extract of E. indica has the ability to alter HHV1 replication cycle at almost all stages and reduce progeny infectivity.